Holding Time pada Sifat Fisik Pengelasan SMAW Baja ASTM-A36 melalui Uji Penetran - Yoga Mangun Wirajaya; Nur Yanu Nugroho; Bagiyo Suwasono (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
In the industrialized world, low-carbon steel was often used as a construction material. One of the problems obtained in the low carbon steel welding process was its nature susceptible to shakes. The minimize the formation of residual voltage in the connection area (Heat Affected Zone) can be done by the Post Weld Heat Treatment (PWHT) process The purpose of this study was to find out the effect caused by variations in heat treatment on heating steel ASTM A36 (Holding Time) to penetrant tests and determine the suitable temperature given to ASTM A36 steel after the welding process. The PWHT process was carried out with several variations of Holding Time, namely 1 hour, 2 hours, and 3 hours at 400 °C. Based on penetrant testing showed that the best value in Holding Time was 3 hours with no appearance of porosity defects